Evaluation of Perinatology Nursing Certificate Program - POTUR, DİLEK; YILDIZ, HATİCE; DEMİRCİ, NURDAN; CAN GÜRKAN, ÖZLEM; EKŞİ GÜLOĞLU, ZÜBEYDE (ELSEVIER SCIENCE BV, 2012)
Due to reasons connected with pregnancy and labour, each year approximately 600,000 women (lie in the world without having any other health problems. Reducing the number of mother and baby deaths is among the objectives of the Ministry of Health in Turkey. To achieve the desired goals, it is necessary to maintain perinatal services without any problems, to standardize care and to provide patient satisfaction. In this issue, health professionals, especially nurses and midwives play an important role. For this reason, thanks to the cooperation of Istanbul Provincial Directorate of Health with Marmara University Faculty of Medical Sciences Nursing School Department of Obstetrics and Gynecology Nursing, training was planned to educate nurses and midwives working in the field of Perinatology, who have an important role in woman health. Objective: The training aims to educate the nurses and midwives who work in the perinatal field, in the importance of women's health in order to make them more competent in the service they provide. Material and Method: A prospective intervention was planned and implemented as a study. A total of 129 midwives and nurses who work in the perinatology units of hospitals in Istanbul that are affiliated to the Ministry of Health, and who completed the Perfriatology Nursing Certificate Program, including 80 hours theoretical and 80 hours clinical practice, constituted the sample of this study. The study was implemented six times between April 2009 and November 2010, and in each program, 20-25 midwives/nurses received training. Data was collected via a questionnaire, a theoretical and practical evaluation form, a post-education three months evaluation form, and preliminary testing before and final testing after the training.Findings: It was determined that the average age of the participants was 32.10 +/- 5.92 and their average work duration was 11.23 +/- 7.31. While the theoretical training average preliminary test score was 62.16 +/- 11.60, the final test score average was 89.35 +/- 5.26. In the third month following the training, 43% and 28.8% of the midwives/nurses stated that they observed a development in their level of knowledge and skills respectively. Also, 92.2% of them indicated that the care they provide improved and 84.6% stated that patient satisfaction was affected in a positive way. Result: It was confirmed that training programs devoted to the field of expertise after graduation have a positive effect on the knowledge and skills of employees and on the service they provide.
Keywords: Nursing Certificate Program; Perinatologv Nursing; EDUCATION